TINJAUAN HUKUM TENTANG PENGANGKATAN ANAK TERLANTAR DI BALI - Pramana, I Gede Pasek (Jurnal Advokasi, 2017)
Balinese customary law does not have strict rules on who can be adopted as a sentana (child). In general, the adopted child is male and originated from the same clan as the prospective adoptive parents. However, the adoption of a female child who is originated outside of the prospective adoptive parents clan and/or has no family relationship with the prospective adoptive parents  is also sometimes permitted. Nonetheless, Bali customary law in fact does not regulatematters on the neglected children. As a result, Balinese customary people seem like lack of legitimacy if they wish to adopt the neglected children as sentana. On the other side, the state law does provide space for every citizen to adopt neglected children as a form of human rights protection of children. Based on the theory of legal pluralism and the theory of semi-autonomous, the Balinese customary law shall be subject to the laws of the state. Hence, the adoption of the neglected children is actually able to be done by the Balinese customary people and still can be given legitimacy from the state law.